Aplikasi Absensi Cleaning service dengan Metode Model Application Development Life Cycle - Lee, Francka Sakti; Nurprihatin, Filscha; Honni, Honni; Santoso, Andi Putra (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
This research aims to develop an attendance application for staff and supervisors in the cleaning service sector of the diesel engine distributor company. The Analysis, Design, Implementation, and Testing (MADLC) method is employed as the primary approach in developing this application. The study focuses on developing a mobile application that can enhance operational efficiency and attendance management in the diesel engine company environment. The first stage, analysis phase is conducted to understand user needs and determine the required features. The design phase involves designing intuitive and user-friendly User Interface (UI) and User Experience (UX). The implementation of the application is carried out using the latest mobile technology to ensure smooth operation across various devices. The final stage, testing phase, involves blackbox testing to verify the functionality and performance of the application. This testing includes functionality tests for the attendance menu, accurate attendance recording, clarity and accuracy of QR code scanning, and the quality of the selfie photo. The test results are used to ensure that the application meets quality standards before being implemented widely. This application is expected to make a positive contribution to improving attendance management, operational efficiency, and productivity in the diesel engine distributor company, as well as serving as a foundation for further research and development in the future.